Natural matrix reinforced with a coordination compound and magnetic nanoparticles to remove organic contaminants from water - Helen Paola Toledo-Jaldin; Alien Blanco-Flores; Delia Monserrat Ávila-Márquez; Oscar Roberto Montes-Moreno; Alfredo Rafael Vilchis-Nestor; Gustavo López-Téllez; Alejandro Dorazco-González (Adsorption Science & Technology)
Sugarcane bagasse, a metal-organic framework, and magnetite nanoparticles form a composite that can be used as absorbent materials for the removal of three pesticides (atrazine, carbofuran, and iprodione). Magnetite nanoparticles were synthesized, functionalized, and supported on the SCB while the metal-organic framework grew on the surface. The adsorption process was performed in water; the pH was close to 7, the room temperature was 23 °C, and the separation of the material was promoted by a magnetic field. The maximum adsorption capacities of the composite were 52.38 mg g −1 for iprodione, 55.45 mg g −1 for atrazine, and 48.03 mg g −1 for carbofuran. The adsorption process occurs through hydrogen bridges with certain steric impediments owing to the ramifications and large sizes of the molecules involved.